Research of growth-regulating activity of some coordination compounds of spirokarbon on plants (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Investigation of the growth-regulating effect of coordination compounds of spirokarbon was performed on seeds of tomatoes (Solanum lycopersicum L.) varieties "Newbie", winter wheat (Triticum aestivum L.) varieties "Zemlyachka Odessa", sunflower (Helianthus annuus L.) varieties "Gourmand" and winter barley (Hordeum L.) varieties "Decent". Phytohormonal impact on monocotyledons was more prominent than on dicotyledons. Stimulating effect on almost all biometric parameters of winter wheat was observed.
Keywords: growth controlling agents, spirokarbon, coordination compounds, biometrics, phytohormonal аctivity.